Improving maternal and child nutrition in China: an analysis of nutrition policies and programs initiated during the 2000-2015 Millennium Development Goals era and implications for achieving the Sustainable Development Goals - Xin Huang; Bo Yang; Qin Liu; Ruilin Zhang; Shenglan Tang; Mary Story (BMC, 2020)
Abstract Background Although good progress was made in maternal and child nutrition during the Millennium Development Goals (MDGs) era, malnutrition remains one of the major threats on global health. Therefore, the United Nation set several nutrition-related goals in the Sustainable Development Goals (SDGs). There is much to be learned from individual countries in terms of efforts and actions taken to reduce malnutrition. China, as a developing country, launched a number of nutrition improvement policies and programs that resulted in dramatic progress in improving maternal and child nutrition during the MDGs era. This study explored the impact, experiences, and lessons learned from the nutrition policies and programs initiated in China during the MDGs era and implications to achieve the SDGs for China and other developing countries. Method The CNKI database and official websites of Chinese government were searched for reviews on nutrition-related policies and intervention programs. A qualitative study was conducted among key informants from the Chinese government, non-governmental organizations (NGOs), and universities for two major national nutrition intervention programs. Results The literature review documented that during the MDGs era, six nutrition policies and eight trans-province and nationwide nutrition intervention programs collectively made good progress in improving maternal and child nutrition in China. Nutrition policies tended to be targeted at infants and children, with less attention on reproductive and maternal nutrition. Nutrition intervention programs focused primarily on undernutrition and have achieved positive results, while for breastfeeding improvement and prevention and control on overweight and obesity were limited. Results from the qualitative study indicated that effective nutrition program implementation was facilitated through the cooperation of multiple sectors and by the government and NGO partnerships, however, still face challenges of insufficient operational funds from local governments and inadequacy of program monitoring and management. Conclusion Nutrition policies and intervention programs promulgated in China during the MDGs era have made major contributions to the rapid decline of undernutrition and are in line to achieve the SDGs related to child wasting, stunting, low birth weight, and anemia in reproductive-age women. However, appropriate policies and program implementation are needed to improve exclusive breastfeeding rates and reduce obesity to achieve the SDGs in years to come.